EVALUASI KINERJA KARYAWAN LEVEL PELAKSANA SATUAN PENGAMANAN PADA PERGURUAN TINGGI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - setiawan, aries (Jurnal Transformatika, 2019)
Higher education has several elements of human resources; one of these elements is at the implementing level, namely the security unit or security guard. In self-reliant activities in work environment, this element functions as industrial security or security in the university environment. It is necessary to have a performance evaluation for the security unit that is useful to measure the success of certain targets of an agency; evaluation includes the self-value of each security unit including the variables of knowledge, skills, behavior, work results, and care to you. The method used for performance evaluation the security unit is Simple Additive Weighting. Based on the results of the test it was found that the alternative a7 occupies the highest rank with a value of 80.33 with details of the value of 4 as many as 6 aspects (c3, c10, c16, c19, c24), value 3 as many as 15 aspects (c2, c4, c5, c7, c8, c9 , c11, c12, c14, c15, c17, c18, c20, c23) and the value of 2 in 3 aspects (c1, c6, c13) exceeds alternative a20 with a number of values 4 more than a7, this is influenced by the weight of each aspect.